OXTR overexpression leads to abnormal mammary gland development in mice. Issue 2 (November 2018) - Li, Dan; Ji, Yan; Zhao, Chunlan; Yao, Yapeng; Yang, Anlan; Jin, Honghong; Chen, Yang; San, Mingjun; Zhang, Jing; Zhang, Mingjiao; Zhang, Luqing; Feng, Xuechao; et al.
Abstract : Oxytocin receptor (OXTR) is a G-protein-coupled receptor and known for regulation of maternal and social behaviors. Null mutation (Oxtr −/− ) leads to defects in lactation due to impaired milk ejection and maternal nurturing. Overexpression of OXTR has never been studied. To define the functions of OXTR overexpression, a transgenic mouse model that overexpresses mouse Oxtr under β-actin promoter was developed ( ++ Oxtr ). ++ Oxtr mice displayed advanced development and maturation of mammary gland, including ductal distention, enhanced secretory differentiation and early milk production at non-pregnancy and early pregnancy. However, ++ Oxtr dams failed to produce adequate amount of milk and led to lethality of newborns due to early involution of mammary gland in lactation. Mammary gland transplantation results indicated the abnormal mammary gland development was mainly from hormonal changes in ++ Oxtr mice but not from OXTR overexpression in mammary gland. Elevated OXTR expression increased prolactin-induced phosphorylation and nuclear localization of STAT5 (p-STAT5), and decreased progesterone level, leading to early milk production in non-pregnant and early pregnant females, whereas low prolactin and STAT5 activation in lactation led to insufficient milk production. Progesterone treatment reversed the OXTR-induced accelerated mammary gland development by inhibition of prolactin/p-STAT5 pathway. Prolactin administration rescued lactation deficiency through STAT5 activation. Progesterone plays a negative role in OXTR-regulated prolactin/p-STAT5 pathways. The study provides evidence that OXTR overexpression induces abnormal mammary gland development through progesterone and prolactin-regulated p-STAT5 pathway.